PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Survei pada Dinas Koperasi UKM Kota Surakarta) - Apri Yanto; Alwi Suddin; Rahayu Triastity (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance of the influence of work discipline and work environment on employee performance with motivation as a moderating variable. Type of data that is using qualitative data and quantitative data. Data sources used are primary and secondary data sources. The study population was the staff of the Surakarta City UKM Cooperative Office. The technique of collecting data using a questionnaire. The data analysis technique used is instrument test, classic assumption test, multiple linear regression, t test, f test, coefficient of determination and absolute difference test. The results of this study indicate that work discipline has a significant effect on employee performance. The work environment has a significant effect on employee performance. Motivation has a significant effect on employee performance. Motivation moderates work discipline and motivation does not moderate the work environment.